Pracownicy katolickich poradni rodzinnych. Aspekt kanoniczno-pastoralny - Adamczyk, Jerzy (Ius Matrimoniale, 2014)
The author of this article has focused on an important problem having a canonical and pastoral aspect, namely on the issue of employees of Catholic family counselling centres. The purpose of the article was to show the need for Catholic family counselling as well as to depict legal and pastoral issues related to family counselling employees: their qualifications and formation. Adequately prepared employees are of utmost importance in Catholic family counselling, as thanks to them this sector of pastoral work will contribute to the fact that the state of marriage will retain the Christian spirit and it will keep improving.